Recent Advances in CuInS2-Based Photocathodes for Photoelectrochemical H2 Evolution - Yoon, Noyoung; Joo, Oh Shim; Chae, Sang Youn; Park, Eun Duck (Nanomaterials, 2023)
Photoelectrochemical (PEC) H2 production from water using solar energy is an ideal and environmentally friendly process. CuInS2 is a p-type semiconductor that offers many advantages for PEC H2 production. Therefore, this review summarizes studies on CuInS2-based PEC cells designed for H2 production. The theoretical background of PEC H2 evolution and properties of the CuInS2 semiconductor are initially explored. Subsequently, certain important strategies that have been executed to improve the activity and charge-separation characteristics of CuInS2 photoelectrodes are examined; these include CuInS2 synthesis methods, nanostructure development, heterojunction construction, and cocatalyst design. This review helps enhance the understanding of state-of-the-art CuInS2-based photocathodes to enable the development of superior equivalents for efficient PEC H2 production.
Keywords: cocatalyst; copper indium sulfide; heterojunction; hydrogen evolution reaction; photoelectrochemical cell